Cain's justice [large type] - Vaughan, Robert, 1937-2024 (Vaughan, Robert, 1937-2024. Lucas Cain book., 2025)
"When Deputy US Marshal Lucas Cain and Deke Pauley forge a partnership on the dusty bounty hunting trail, their camaraderie faces its ultimate test when Deke is Mercilessly gunned down. Committing to a grueling journey on foot, Lucas's path collides with the elegant private rail car of Leah Davenport. Leah presents him with an offer that could change the course of his destiny --- a lucrative bounty for locating and safely returning a kidnapped child to his father. But with unforeseen challenges rising from a surprising source, Lucas begins to wonder --- in the business of bounty hunting, is solitude his only reliable ally?"--Back cover.